Pengaruh Substitusi Air dengan Ekstrak Daun Binahong (Anredera cordifolia) Terhadap Karakteristik Sensori dan Fisikokimia Es Krim - Violalita, Fidela; Nasution, Nabilah Savitri; Nirwana, Nila Liling; Yanti, Henny Fitri; Evawati, Evawati; Roza, Irwan (Pro Food, 2025)
Ice cream is classified as a popular frozen product consisting of a mixture of milk, cream, and various other ingredients. To provide functional value, innovation was achieved by utilizing binahong leaf extract. The high antioxidant and chlorophyll content in binahong leaf extract makes it a potential natural coloring agent for ice cream. This study aimed to analyze the quality of ice cream substituted with binahong (Anredera cordifolia) leaf extract in terms of sensory and physicochemical characteristics. Four substitution treatments of water with binahong leaf extract in ice cream 25%, 50%, 75%, and 100% were analyzed using the hedonic sensory method to determine the best formulation. Analysis of variance (ANOVA) and Duncan's Multiple Range Test (DMRT) at a significance level of 0.05% were used to analyze the data obtained. Sensory analysis results showed that the 75% binahong leaf extract treatment provided the highest level of preference among panelists. The preference scores for the binahong leaf extract ice cream were appearance 4.07 (slightly liked), color 4.20 (slightly liked), aroma 3.70 (slightly liked), taste 4.30 (slightly liked), and texture 4.00 (slightly liked). Physicochemical analysis of the best treatment showed fat content of 5.18%, sugar content of 16.55%, protein content of 3.31%, antioxidant level of 16.93% inhibition, flavonoid content of 11.45 ppm, crude fiber content of 0.0685%, total solids of 34%, and overrun of 89.59%. Based on the standards in SNI 01-3713-1995, the quality of the resulting ice cream met the established requirements.